IMPROVING WRITING SKILL THROUGH SIMULTANEOUS ROUNDTABLE TECHNIQUE COMBINED WITH PICTURES OF THE ELEVENTH-GRADE STUDENTS - Nengah Dwi Handayani; Ida Ayu Praba Iswari Dewi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2025)
This study aims to determine the improvement of writing skills of eleventh grade students of SMKN 5 Denpasar through the Simultaneous Roundtable technique combined with pictures. The subjects were grade XI DKV students of SMKN 5 Denpasar in the 2024/2025 academic year. The 26 students consisted of 19 males and 12 females. The design used was a classroom action research design, with the application of the Simultaneous Roundtable technique in two cycles. Data collection was carried out using tests and questionnaires. The results showed that Simultaneous Roundtable combined with pictures can improve students' writing skills, especially in recount texts. This can be seen from the increase in students' average scores before and after the implementation of the action through the pre-test and post-test. In the pre-test conducted at the beginning before the technique was used, the average pre-test score was 47.23. Then, the score increased to 72.34 in post-test 1 and 83.69 in post-test 2. In addition, the questionnaire given showed a positive response from the subjects towards the implementation of the Simultaneous Roundtable technique combined with images during the teaching and learning process. In summary, this study shows that the writing ability of eleventh grade students of SMKN 5 Denpasar in the 2024/2025 academic year can be improved through the Simultaneous Roundtable technique combined with images.